Islamic Da’wah on Instagram: Impacts and Challenges Among Islamic Communication and Broadcasting Students at UIN Sumatera Utara - Zurrahman Rifqi Nainggolan; Nashrillah Nashrillah (Yayasan Maslahatul Ummah Ilal Jannah, 2026)
This study aims to explore the utilization of Instagram as a medium for fulfilling religious information needs among Islamic Communication and Broadcasting (KPI) students at UIN Sumatera Utara, specifically concerning academic practices, religious learning, da’wah dissemination, and the formation of critical attitudes toward Islamic content in the digital space. This research employs a qualitative method with a phenomenological approach. Data were gathered through observation, semi-structured interviews, and documentation involving students who actively use Instagram as a source of religious information, a platform for Islamic learning, and a medium for da’wah outreach. The results indicate that KPI students at UIN Sumatera Utara utilize Instagram as an academic channel integrated into the learning process and Islamic communication practices. Instagram is leveraged to acquire religious information, da’wah messages, and academic-related materials. One of the prominent da’wah channels identified is the @dakwah_tauhid account, perceived as engaging, creative, accessible, and inspirational in fostering spiritual closeness to Allah. However, the findings also reveal that not all da’wah content on Instagram is accepted unconditionally. Students critically filter, evaluate, and verify religious content against credible sources and religious authorities, aligning with the scientific foundations of Islamic Communication and Broadcasting. Consequently, Instagram functions not only as a medium for religious information fulfillment but also as a space for digital learning and da’wah, as well as an arena that demands digital literacy and critical awareness in interpreting religious messages.